Participatory decision making in secondary schools: case of students’ involvement in Mwala division, Kenya - Mulwa, David; Maiyo, Julius (My University, 2010)
The study was an investigation of the participation in decision making by secondary schools students in Mwala division, Mwala district. The purpose was to identify the key decision makers in Secondary schools and the extent to which students were involved in decision making as far as curriculum and instruction, students’ management and welfare, and school-community relations were concerned. The study was based on the Normative Model of Group Decision making. The study hypothesized that schools would largely involve students in decision making in order to avert major crises like school strikes. The study used data collected from three secondary schools randomly selected from 10 public secondary schools in Mwala division. A sample of 80 students was selected randomly to represent the schools. A descriptive survey research design was adopted for the study. Data were sourced from the students by use of a questionnaire. Data was analyzed by use of descriptive analysis techniques which involves frequencies, percentages, means and standard deviations. It was established that students participated least in decision making concerning curriculum and instruction, and students’ management and welfare but largely participated in making decisions concerning school community relations. More than 95% of the students indicated that they would like to participate more in decision making.
Keywords: Decision; Decision making; Decision making process; Involvement.